Rapid Clinical Progression and Its Correlates Among Acute HIV Infected Men Who Have Sex With Men in China： Findings From a 5-Year Multicenter Prospective Cohort Study - Zhang, Jing; Huang, Xiao-jie; Tang, Wei-ming; Chu, Zhenxing; Hu, Qinghai; Liu, Jing; Ding, Haibo; Han, Xiaoxu; Zhang, Zining; Jiang, Yong-jun; Geng, Wenqing; Xia, Wei; et al. (Frontiers in Immunology, 2021)
Background: In the “treat all” era, there are little data on the nature of HIV clinical progression in middle-income countries. The aim of the current study was to prospectively analyze the clinical progression of HIV and its indicators among men in China with acute HIV who have sex with men. Methods: From 2009–2014 a total of 400 men with acute HIV infection (AHI) were identified among 7,893 men who have sex with men via periodic pooled nucleic acid amplification testing, and they were assigned to an AHI prospective cohort in Beijing and Shenyang, China. Rapid progression was defined as two consecutive CD4+ T cell counts < 350/µL within 3–24 months post-infection. Kaplan Meier and Cox regression analyses were conducted to identify predictors of rapid progression. Results: Among 400 men with AHI 46.5% were rapid progressors, 35.1% reached rapid progressor status by 12 months post-infection, and 63.9% reached rapid progressor status by 24 months. Rapid progression was associated with herpes simplex-2 virus coinfection (adjusted hazard ratio [aHR] 1.7, 95% confidence interval [CI] 1.2–2.3], depression (aHR 1.9, 95% CI 1.5–2.6), baseline CD4+ T cell count < 500/μL (aHR 3.5, 95% CI 2.4–5.1), higher baseline HIV viral load (aHR 1.6, 95% CI 1.2–2.3), acute symptoms lasting ≥ 2 weeks (aHR 1.6, 95% CI 1.1–2.2), higher body mass index (aHR 0.9, 95% CI 0.9–1.0), higher HIV viral load (aHR 1.7, 95% CI 1.4–2.1), set point viral load at 3 months (aHR 2.0, 95% CI 1.6–2.5), each 100-cell/μL decrease in CD4+ T cell count at 3 months (aHR 2.2, 95% CI 1.9–2.5), and baseline routine blood tests including white blood cell count < 5.32, hemoglobin ≥ 151, mean corpuscular hemoglobin ≥ 30.5, hemoglobin concentration ≥ 342, mean platelet count ≥ 342, lymphocytes ≥ 1.98, and mixed cell count ≥ 0.4 (all p < 0.05). Conclusion: Almost half of the patients underwent rapid clinical progression within 2 years after HIV infection. A treat-all policy is necessary and should be strengthened globally. Rapid progression can be identified via simple indicators such as body mass index and routine blood test parameters in low and middle-income countries.